Biochemical and oxidative stress markers in the liver and kidneys of rats submitted to different protocols of anabolic steroids - Dornelles G.L. (2017)
© 2016, Springer Science+Business Media New York.The objective of this study was to evaluate the effects of different protocols (P1, P2, and P3) of boldenone undecylenate (BU) and stanozolol (ST) on markers of liver and kidney function and variables of oxidative stress in these organs. For this, 54 male Wistar rats were divided into nine groups of six animals each. Each animal received intramuscularly 5.0 mg kg−1 of BU or ST once a week for 4 weeks (P1); 2.5 mg kg−1 of BU or ST once a week for 8 weeks (P2); and 1.25 mg kg−1 of BU or ST once a week for 12 weeks (P3). For each protocol, a control group was used, and they received 0.1 ml of olive oil intramuscularly. Blood and fragments of liver and kidney were collected for alanine aminotransferase activity (ALT), alkaline phosphatase, albumin, creatinine, cholesterol, total protein, triglycerides, urea, reactive oxygen species, thiobarbituric acid reactive substances, total thiols, and glutathione evaluation. The results show that the BU in doses of 5 (day 30) and 2.5 mg kg−1 (day 60) changes the ALT seric activity, possibly showing a hepatotoxic effect. High doses of BU may lead to increased levels of cholesterol (protocol P1) possibly due to inhibition of the normal steroid biosynthesis process. All protocols used caused changes in the redox balance of the organs studied (except in the liver, protocol P2), which indicates that these drugs might be harmful even at low doses.